The right to environmental cleanliness through waste management in West Lampung Regency - Muhammad Zahid Alim; Agus Triono; Rifka Yudhi (Annals of Justice and Humanity, 2023)
Purpose: This study aims to examine waste management problems in the Lampung Barat Regency. Research Methodology: This study employed a normative method using a descriptive analysis approach. Secondary data were acquired through meticulous literature review and subjected to qualitative analysis. The secondary data in question include Law Number 18 of 2008 concerning Waste Management, Law Number 32 of 2009 concerning Environmental Protection and Management, West Lampung Regency Regional Regulation Number 4 of 2018 concerning Waste Management, and West Lampung Regent Regulation Number 31 2022 Regarding Waste Reduction Guidelines. Rigorous literature selection ensured data validity. The outcomes of the analysis served as the basis for accurate conclusions within the research. Results: Fulfillment of the right to a clean environment through waste management is a reference for the government and local governments implementing the principles of Good Environmental Governance with a growth orientation awareness for the community about a good and healthy living environment. Limitations: Waste management remains an unresolved problem. There are several laws and regulations that correlate with waste management in Indonesia, namely Law No. 32 of 2009 concerning Environmental Protection and Management and several other laws. Contribution: Fulfilling the right to a clean environment through waste management refers to three legal systems that are a combination of components: structure, substance, and culture. This is related to law enforcement in waste management and can be studied from two perspectives: preventive and repressive.